Synergy from Pfizer’s Acquisition of Seagen Based on the Balanced Scorecard - He, Yihang (Transactions on Economics, Business and Management Research, 2024)
Evaluating the merger's synergistic effects based on the Balanced Scorecard theory is a common measure to analyze the effectiveness. This paper selects the classic pharmaceutical merger case of Pfizer's acquisition of Seagen as an example. This acquisition is extremely important for Pfizer as a decision to reverse the current downturn in revenue. Initially, the paper introduces the theory of synergistic effects and the Balanced Scorecard theory, explaining the relationship between the three types of synergistic effects and the four dimensions of the Balanced Scorecard, laying the groundwork for the subsequent discussion. Then, it introduces the background, motivation, and process of Pfizer's acquisition of Seagen, summarizing the characteristics of this case. After reviewing the case background, the paper sets specific evaluation indicators for the three synergistic effects, considering the characteristics of pharmaceutical companies and following the four dimensions of the Balanced Scorecard. Ultimately, based on these indicators, it evaluates the synergistic effects of Pfizer's acquisition of Seagen and offers recommendations. Through this case study, the paper finds that the synergistic effects after Pfizer's acquisition are not significant. Even profitability and new drug sales improved, other indicators used to measure synergistic effects showed little change or a downward trend.